Teachers' Perception towards Enhancement of Lower Basic Pupils’ Academic Performance through Home-Grown School Feeding Programme - OGUNJIMI, Mayowa Olurotmi; ADETEJU, Kehinde Adeyemi (Ilorin Journal of Education, 2024)
The study examined the perception of teachers towards enhancement of lower basic pupils’ academic performance through home-grown school feeding programme in Irepo Local Government of Oyo state. The population was all the 134 lower basic teachers in the area of study. 100 teachers from 20 primary schools, 5 teachers were selected from each of the schools using Yaro Yamane's formula. Data were taken through the use of a structured questionnaire titled: Teachers Perception on Enhancement of Pupils Academic Performance through Home-grown School Feeding (TPEPAPHSF) and its psychometric properties were assessed through content validity and test-retest reliability with a coefficient value of 0.81 respectively. Data collected were analyzed using mean, 2.50 benchmark was used to answer research question while t-test and ANOVA were used to analyze research hypotheses at 0.05 level of significance. The results shown that teachers’ perception was positive by the weighted mean of 2.61. However, their opinions on the practical aspect of academic were negative on the basis that home grown school feeding programme does not enhance pupils’ abilities to undertake practical task independently. Also, it was shown that teachers’ perception does not depend on age qualification except for gender. Consequently, it was recommended that teachers should be consistently involved in the schemes of system and drastically empowered through various capacity building programmes to explore and enjoy their best. More importantly, practical aspect in the system needs to be given workable attention.